PETA GERAKAN SYI’AH DI KALIMANTAN SELATAN - humaidy, Humaidy (Pascasarjana UIN ANTASARI Banjarmasin, 2014)
This article traces back the entry of the Shi?a in South Kalimantan through the inclusion of Islamic Wujudiyah (panentheism) Sufismwhich was firstspreadin the kingdom of Banjar. This isdue to the similaritybetween Wujudiyah Sufism with the concept of Irfan in Shi'a. However, the influence of Shia in South Kalimantan suffered a setback atthe era of Syekh Muhammad al-Banjari Arsyad (1710-1812 AD). According to Habib Ali,Shia began to revive in South Kalimantan after the Iranian revolution in 1979. Ja?fari school of thought (madhabs) is the growing Shiah in South Kalimantan. The Developmentof Shi?a in South kalimantan faces manychallenges since Muslims in South Kalimantan have a strong belief in Sunni